Class matters - Fergal Finnegan; Barbara Merrill (Universidade de Lisboa, 2024)
Over the past sixty years social class and social class analysis has been a key focus of educational research in many countries and in different educational institutional contexts and drawing on a range of theoretical approaches such as Weberian, Marxist, Durkheimian etc. In particular research and literature has illuminated the power of education to reproduce and perpetuate class inequalities. Historically class has been approached in a different way in adult education research and practice with a greater focus on agency and lived experience. This is connected to the influence of radical adult education on scholarship and pedagogy in some countries such as the Workers Educational Association in the UK, the folk high school movement in Scandinavia, and popular education in Latin America which were connected to democratic and socialist working-class movements which promoted class solidarity and social transformation (albeit understood in very varied ways). To a large extent this horizon has disappeared, or at least been reconfigured. Research on social class is also increasingly recognising that class does not exist in isolation but intersects with other forms of inequality such as gender and race. Just as importantly studies indicate that although class relations and politics are changing class still matters. However, while there is a body of studies on working class experience and a strong interest in questions of inequality in contemporary adult education it is striking how rarely class in foregrounded and the extent to which adult education scholarship is disconnected from new work on class in social science. This special issue aims to spark discussion and debate on this topic.